The effect of CO−H2O collisions in the rotational excitation of cometary CO. Issue 1 (25th January 2020) - Faure, A; Lique, F; Loreau, J
ABSTRACT: We present the first accurate rate coefficients for the rotational excitation of CO by H2 O in the kinetic temperature range 5–100 K. The statistical adiabatic channel method (SACM) is combined with a high-level rigid-rotor CO−H2 O intermolecular potential energy surface. Transitions among the first 11 rotational levels of CO and the first 8 rotational levels of both para -H2 O and ortho -H2 O are considered. Our rate coefficients are compared to previous data from the literature and they are also incorporated in a simple non-LTE model of cometary coma including collision-induced transitions, solar radiative pumping and radiative decay. We find that the uncertainties in the collision data have significant influence on the CO population distribution for H2 O densities in the range 10 3 –10 8 cm −3 . We also show that the rotational distribution of H2 O plays an important role in CO excitation (owing to correlated energy transfer in both CO and H2 O), while the impact of the ortho-to-para ratio of H2 O is found to be negligible.